C# 7.0 : all-in-one / John Mueller; Bill Sempf; Chuck Sphar - Mueller, John
C# know-how is a must if you want to be a professional Microsoft developer. It's also good to know a little C# if you're building tools for the web, mobile apps, or other development tasks. C# 7.0 All-in-One For Dummies offers a deep dive into C# for coders still learning the nuances of the valuable programming language. Pop it open to get an intro into coding with C#, how to design secure apps and databases, and even pointers on building web and mobile apps with C#. C# remains one of the most in-demand programming language skills.